Ethanolic Extract of Ocimum sanctum Linn. Inhibits Cell Migration of Human Lung Adenocarcinoma Cells (A549) by Downregulation of Integrin αvβ3, α5β1, and VEGF - Kustiati, Ulayatul (MDPI, 2022)
Adenocarcinoma lung cancer is a type of non-small cell lung carcinoma (NSCLC), which accounts for 85% of lung cancer incidence globally. The therapies that are being applied, both conventional therapies and antibody-based treatments, are still found to have side effects. Several previous studies have demonstrated the ability of the ethanolic extract of Ocimum sanctum Linn. (EEOS) as an ethnomedicine with anti-tumor properties. The aim of this study was to determine the effect of Ocimum sanctum Linn. ethanolic extract in inhibiting the proliferation, angiogenesis, and migration of A549 cells (NSCLC). The adhesion as well as the migration assay was performed. Furthermore, enzyme-linked immunosorbent assay (ELISA) was used to measure the expression of αvβ3 integrins, α5β1 integrins, and VEGF. The cells were divided into the following treatment groups: control (non-treated/NT), positive control (AP3/inhibitor β3 80 µg/mL), cisplatin (9 µg/mL), and EEOS at concentrations of 50, 70, 100, and 200 µg/mL. The results showed that EEOS inhibits the adhesion ability and migration of A549 cells, with an optimal concentration of 200 µg/mL. ELISA testing showed that the group of A549 cells given EEOS 200 µg/mL presented a decrease in the optimal expression of integrin α5β1, integrin αvβ3, and VEGF.